Simultaneous Silencing of Two Arginine Decarboxylase Genes Alters Development in Arabidopsis - Sánchez-Rangel, Diana; Chávez-Martínez, Ana I.; Rodríguez-Hernández, Aída A.; Maruri-López, Israel; Urano, Kaoru; Shinozaki, Kazuo; Jiménez-Bremont, Juan F. (Frontiers in Plant Science, 2016)
Polyamines (PAs) are small aliphatic polycations that are found ubiquitously in all organisms. In plants, PAs are involved in diverse biological processes such as growth, development, and stress responses. In Arabidopsis thaliana, the arginine decarboxylase enzymes (ADC1 and 2) catalyze the first step of PA biosynthesis. For a better understanding of PA biological functions, mutants in PA biosynthesis have been generated; however, the double adc1/adc2 mutant is not viable in A. thaliana. In this study, we generated non-lethal A. thaliana lines through an artificial microRNA that simultaneously silenced the two ADC genes (amiR:ADC). The generated transgenic lines (amiR:ADC-L1 and -L2) showed reduced AtADC1 and AtADC2 transcript levels. For further analyses the amiR:ADC-L2 line was selected. We found that the amiR:ADC-L2 line showed a significant decrease of their PA levels. The co-silencing revealed a stunted growth in A. thaliana seedlings, plantlets and delay in its flowering rate; these phenotypes were reverted with PA treatment. In addition, amiR:ADC-L2 plants displayed two seed phenotypes, such as yellow and brownish seeds. The yellow mutant seeds were smaller than adc1, adc2 mutants and wild type seeds; however, the brownish were the smallest seeds with arrested embryos at the torpedo stage. These data reinforce the importance of PA homeostasis in the plant development processes.